HEGEMONI BUDAYA MUSIK BAHASA JAWA DAN GENERASI Z DI ERA DIGITAL - Zulaili, I'in Nur; Putra, Naufal Ananda; Putri, Viona Aurillia (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This research discusses the phenomenon of Javanese music trends on various social media. Songs in Javanese such as Rungkad, Kisinan, Nemen, and Cundamani written by young Indonesians have been able to dominate the music charts in Indonesia with audiences from various circles, including Generation Z. This phenomenon is not only a sign of regional language songs, especially Javanese can compete with foreign songs, but is also a symbol of the integrity of people's love for their homeland, Indonesia. This research aims to show that cultural hegemony as a product of globalization can be used as a reference for society in advancing the nation through music. The method used is a qualitative descriptive approach with a literature study of Javanese songs and data analysis techniques will be strengthened by Roland Barthes' Semiotic theory. The results of this research will show three conclusions. First, the cultural hegemony of Javanese music positively impacts the values, perceptions, and customs of Indonesian people in enjoying music. Second, Generation Z who likes to create, introduce, and share various Javanese music in the digital era shows that Indonesian people are very active, able to be highly competitive, and proud of their national identity. Third, the denotational meaning in various trending Javanese song lyrics represents the hearts of Generation Z, some of which tell stories about someone's futile struggle, love story, heartbreak, and being betrayed by a lover until finding the best gem.